2021
DOI: 10.1177/1060028021994621
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Use of Cangrelor After Percutaneous Coronary Intervention in Patients Requiring Mechanical Circulatory Support

Abstract: Background: Patients with cardiogenic shock after percutaneous coronary intervention (PCI) may require mechanical circulatory support (MCS). The combination of dual antiplatelet therapy with cangrelor and continuous anticoagulation required for MCS may increase the risk of bleeding. Objective: The objective of the study is to describe the complications and outcomes of patients who received cangrelor during MCS following PCI. Methods: This is a single-center, retrospective, observational case series of 17 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…In addition, further studies should evaluate the optimal DAPT strategy, including either omitting aspirin, using clopidogrel only, or administering reduced dose cangrelor while the Impella ® device is in place, 17 to mitigate the risk of bleeding associated with triple antithrombotic therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, further studies should evaluate the optimal DAPT strategy, including either omitting aspirin, using clopidogrel only, or administering reduced dose cangrelor while the Impella ® device is in place, 17 to mitigate the risk of bleeding associated with triple antithrombotic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that a cangrelor dose <0.75 µg/kg/min may be beneficial in reducing the risk of bleeding in patients receiving on Impella ® or ECMO. 17 The preferred antiplatelet agent and optimum dosing strategies remains to be determined. There are several limitations to our study, including its observational, retrospective design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, our BARC 3-5 bleeding event rates (50%) were the lowest among reports on cangrelor use in VA-ECMO patients, that range between 67-100% (Figure 1B). 2,15,18 Specifically, a cohort comprising CS shocks patient on VA-ECMO who received PCI found a 77% rate of BARC 3-5 bleeding; in this cohort cangrelor was chiefly combined with aspirin (in 85%) and heparin (in 92%). 2 Katz et al 15 found a 67% rate of BARC 3-5 bleeding in a cohort of PCI patients with CS on VA-ECMO who received aspirin, heparin, and cangrelor titrated by platelet function test.…”
Section: Discussionmentioning
confidence: 99%
“…2,15,18 Specifically, a cohort comprising CS shocks patient on VA-ECMO who received PCI found a 77% rate of BARC 3-5 bleeding; in this cohort cangrelor was chiefly combined with aspirin (in 85%) and heparin (in 92%). 2 Katz et al 15 found a 67% rate of BARC 3-5 bleeding in a cohort of PCI patients with CS on VA-ECMO who received aspirin, heparin, and cangrelor titrated by platelet function test. Finally, in a cohort of patients receving cangrelor as bridging to surgery or if oral medications were contraindicated, BARC 3-5 bleeding rates occurred in 100% in the VA-ECMO subgroup: no other details on antithrombotic therapy in this subgroup are available.…”
Section: Discussionmentioning
confidence: 99%